Penerapan Konseling Individu dengan Teknik Client Centered untuk Mengatasi Self-Efficacy (Studi Kasus Klien Anak Korban Broken Home) - Furqon, Addis Al; Razzaq, Abdur (Journal of Society Counseling, 2024)
This research is entitled "Application of Individual Counseling Using Client Centered Techniques to Overcome Self-Efficacy in Children Victims of Broken Homes." Self-efficacy is an individual's belief in his abilities, in that the individual has the ability to organize and complete certain tasks. This research aims to determine the description of self-efficacy in children who are victims of a broken home, client "A" and to determine the application of individual counseling using client-centered techniques to overcome self-efficacy in children who are victims of a broken home, client "A". This research uses a qualitative approach with a case study research method. The subject in this research is client "A". The data collection technique used in this research consists of 3 data collection techniques, namely: observation, interviews and documentation. The data analysis techniques used in this research are data reduction, data presentation, and drawing conclusions. The results of the research show that the description of self-efficacy experienced by client "A" is: not sure that he can complete difficult tasks or certain tasks because he is not confident in his abilities and potential, not sure he can motivate himself because he has no motivation since the divorce. his parents, not confident in the effort and hard work he has done because he easily gives up, not confident in his abilities when facing obstacles because he feels pessimistic and unable to recover from failure, not confident in completing tasks in various situations because client "A" feels panic and haste when faced with a task in a difficult situation. The application of individual counseling using client centered techniques is carried out in 6 meetings within 45 minutes per meeting. The implementation of the individual counseling process is carried out in three stages, namely, the initial stage, the core stage or work stage, and the final stage.